Crave : Charm - Book 5 - Wolff, Tracy (Shrewsbury, PA : Entangled Teen, an imprint of Entangled Publishing LLC, 2022)
Unravel the mystery of the missing four months between Grace and Hudson--when she finds herself trapped with the last boy she ever expected, and certainly the most obnoxious one shes ever met. If he doesnt shut up, she just might kill him...if she doesnt kiss him first.
Keywords: Vampires -- Fiction; Boarding schools -- Fiction; Schools -- Fiction; Teenagers -- Fiction; Vampire fiction; Parnormal fiction; Romance fiction; School fiction; Fantasy fiction; Fiction; Juvenile works; Paranormal fiction; Romance fiction; Young adult works